FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERSEPSI KESELAMATAN PADA PEJALAN KAKI PENGGUNA PELICAN CROSSING JL. PEMUDA KOTA SEMARANG - Fahmi Aditya; Ekawati Ekawati; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2020)
Safety perception is a process of individuals that describe their impressions to the safety aspects of the environment. Some factors that affect safety perception on pedestrians are: individual characteristics, situational conditions, and environmental conditions. The study were conducted on pedestrians’ safety perception on pelican crossing that located in Jl. Pemuda, Semarang. The aim of this study is to analyze the factors that correlated with pedestrians’ safety perception. Methods of the research is analytic survey and observasional with quantitative study approach. Population of the study were all of the pedestrians’ using the pelican crossing on Jl. Pemuda. Sample linear time function was used as sampling method of this study in order to anticipate the population that was unavailable to be calculated. Data were collected using questionnaire and observation on location. The research shows that there were none of the variables that correlated with pedestrians’ safety perception. The variables included are age (p=0,510), sex (p=0,311), time of crossing (p=0,653), crossing method (p=0,544), obedience (p=0,570), conflict with vehicles (p=0,137), and unsafe acts (0,910). The research suggests the need to enforce the law for pedestrian and vehicles. The research also suggest to install the pelican crossing in many other areas of the city within large volume of pedestrian.